Transformation from Millennial Students to Engineers in Engineering Institutions-A Case Study - Sumathi, D.; Kannan, S.; Sudhakara Reddy, S. (Journal of Engineering Education Transformations, 2018)
"It is not what you teach and how you teach It is what your audience learns" Recently the millennial learners occupy the classrooms. These learners are filled with their needs and characteristics. They need collaborative learning experiences, quick feedback and have low tolerance for boredom. The main challenge for the faculty is to keep the learners in the classroom fully engaged, challenged and focused. This paper discusses about the characteristics of millennial learners and the way of using technologies to reach the millennial learners in the classroom. The responsibility of the faculty is to create self-learners and life-long learners.